Interstage mortality in two‐stage elephant trunk surgery. Issue 6 (26th February 2021) - Saeyeldin, Ayman; Gryaznov, Anton A.; Zafar, Mohammad A.; Wu, Jinlin; Mukherjee, Sandip; Vallabhajosyula, Prashanth; Ziganshin, Bulat A.; Elefteriades, John A.
ABSTRACT: Purpose: Diffuse mega‐aorta is challenging. Prior studies have raised concerns regarding the safety of the open two‐stage elephant trunk (ET) approach for extensive thoracic aortic aneurysm (TAA), specifically in regard to interstage mortality. This study evaluates the safety of the two‐stage ET approach for management of extensive TAA. Methods: Between 2003 and 2018, 152 patients underwent a Stage I ET procedure by a single surgeon (mean age 64.5 ± 14.8). Second stage ET procedure was planned in 60 patients (39.4%) and to‐date has been performed in 54 patients (90%). (in the remaining patients, the ET was prophylactic for the long‐term, with no plan for near‐term utilization). Results: In‐hospital mortality after the Stage I procedure was 3.3% (5/152). In patients planned for Stage II, the median interstage interval was 5 weeks (range: 0–14). Of the remaining six patients with planned, but uncompleted Stage II procedures, five patients expired from various causes in the interval period (interstage mortality of 8.3%). There were no cases of aortic rupture in the interstage interval. Stage II was completed in 58 patients (including four unplanned) with a 30‐day mortality of 10.3% (6/58). Seven patients developed strokes after Stage II (12%), and three patients (5.1%) developed paraplegia. Conclusions: The overall mortality, including Stage I, interstage interval, and Stage II was 18.6%. This substantial cumulative mortality for the open two‐staged ET approach for the treatment of extensive TAA appears commensurate with the severity of the widespread aortic disease in this patient group. Fear of interstage rupture should not preclude the aggressive Two‐Stage approach to the management of extensive TAA.